ANALISIS KOMPETENSI SUMBER DAYA MANUSIA DALAM PENGGUNAAN ALAT DIGITALISASI ADMINISTRASI KEPOLISIAN DI POLRES MAMUJU - Natalianus Malotombi; Muhammad Rais Rahmat Razak; Ahmad Mustanir; Rasdiana Mustapa (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
This study aims to analyze human resource competence in using the Indonesian National Police Personnel Information System (SIPP) at Polres Mamuju, focusing on efficiency, effectiveness, transparency, accountability, responsiveness, and participation. The research employs a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The results of this study indicate that the level of efficiency and effectiveness of HR competence at Polres Mamuju in operating the Digitalization Tool of the Indonesian National Police Personnel Information System application is classified as quite good, characterized by the ability to carry out routine tasks efficiently and a basic understanding of digital tool functions, although there are still technical obstacles such as network disruptions and limited understanding of advanced features. The implementation of Police Administration in the form of the Indonesian National Police Personnel Information System application also contributes significantly to improving transparency and accountability in administration through automatic recording systems and real-time reporting, but still requires continuous HR capacity enhancement. In addition, HR responsiveness and participation towards technical obstacles are considered quite good, and the implementation of this technology has reflected the principles of justice and economic efficiency. Nevertheless, obstacles such as limited technical readiness and unequal employee participation indicate the need for strengthening participatory systems, routine training, and infrastructure improvements to support the implementation of inclusive, fair, and sustainable administrative digitalization.